2007
DOI: 10.1530/eje-06-0598
|View full text |Cite
|
Sign up to set email alerts
|

Effects of growth hormone in patients with tibial fracture: a randomised, double-blind, placebo-controlled clinical trial

Abstract: Objective: Investigate whether intervention with GH after tibial fracture enhances fracture healing. Design: Randomised, double-blind, placebo-controlled study in 406 patients (93 women, 313 men, age: 18-64 years) with tibial fracture. Methods: Patients were stratified by tibial fracture (open or closed) and allocated to placebo or GH treatment (15, 30 or 60 mg/kg daily, until clinically assessed healing or until 16 weeks post-surgery). Primary outcome was time from surgery until fracture healing and assessmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
3

Year Published

2008
2008
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 44 publications
(34 citation statements)
references
References 41 publications
0
31
0
3
Order By: Relevance
“…O uso do rhGH sistemicamente em fraturas ósseas já vem sendo estudado, como no trabalho de Raschke et al 18 , que utilizaram o rhGH sistemicamente em pacientes com fraturas de tíbia. Seus resultados mostraram a eficiência do rhGH na cicatrização óssea no grupo de pacientes que receberam um tratamento conservador, não cirúrgico.…”
Section: Discussionunclassified
“…O uso do rhGH sistemicamente em fraturas ósseas já vem sendo estudado, como no trabalho de Raschke et al 18 , que utilizaram o rhGH sistemicamente em pacientes com fraturas de tíbia. Seus resultados mostraram a eficiência do rhGH na cicatrização óssea no grupo de pacientes que receberam um tratamento conservador, não cirúrgico.…”
Section: Discussionunclassified
“…Todos los autores coinciden en su efecto positivo sobre la curación de las fracturas, no obstante, la mayoría han reportado efectos sistémicos adversos 28,29 . Sin embargo, hay pocos estudios sobre su utilización local, y los que se han encontrado, no informan de efectos sistémicos 30 .…”
Section: Factores De Crecimiento Utilizadosunclassified
“…Detailed information on the study design and exposed study population has been reported previously [19]. Briefly, subjects were stratified by the type of fracture, i.e., open or closed.…”
Section: Study Design and Proceduresmentioning
confidence: 99%
“…The baseline characteristics across the treatment groups were similar, with the majority in each treatment group being Caucasian males with a closed tibia fracture; however, race was not recorded at the trial sites in South Africa, which contributed with approximately 30% of the trial population. Further details of the subject demography and accountability have been presented previously [19].…”
Section: Subject Demography and Accountabilitymentioning
confidence: 99%